2017
DOI: 10.3390/su9040669
|View full text |Cite
|
Sign up to set email alerts
|

A Transition to Which Bioeconomy? An Exploration of Diverging Techno-Political Choices

Abstract: Abstract:To date the concept of the bioeconomy-an economy based primarily on biogenic instead of fossil resources-has largely been associated with visions of "green growth" and the advancement of biotechnology and has been framed from within an industrial perspective. However, there is no consensus as to what a bioeconomy should effectively look like, and what type of society it would sustain. In this paper, we identify different types of narratives constructed around this concept and carve out the techno-poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 41 publications
(51 reference statements)
4
139
0
Order By: Relevance
“…For example, the new bioeconomy value chains could trigger societal conflicts if resource efficiency gains, cascading use, residue use and sustainability certification are insufficient to ensure a sustainable supply of biomass [6]. Existing studies, e.g., [7,8] highlight the importance of future research on the economic and societal implications of the bioeconomy, and consequently observe an imbalanced focus on technology and science-based concepts of the bioeconomy in policy and research narratives that neglect socio-political aspects. The narrative about the bioeconomy and its implementation has placed a strong focus on industry and policy [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the new bioeconomy value chains could trigger societal conflicts if resource efficiency gains, cascading use, residue use and sustainability certification are insufficient to ensure a sustainable supply of biomass [6]. Existing studies, e.g., [7,8] highlight the importance of future research on the economic and societal implications of the bioeconomy, and consequently observe an imbalanced focus on technology and science-based concepts of the bioeconomy in policy and research narratives that neglect socio-political aspects. The narrative about the bioeconomy and its implementation has placed a strong focus on industry and policy [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This case-study has shown how easily certain partialities of the public that have a substantial stake in the transition, but have less power, remain "ignored" or are framed according to specific interpretations. This highlights the need for a better, more substantial, involvement of the heterogeneous public, as also stressed by a number of other studies [7,9,10,38]. Chilvers and Longhurst [22] have called for a better analysis of the relationship between the way in which collectives of participation are configured and political openings/closings that occur with respect to models, publics and objects of participation.…”
Section: Main Findingsmentioning
confidence: 96%
“…According to the definition of OECD that focuses on the role of biotechnologies, "a bioeconomy can be thought of as a world where biotechnology contributes to a significant share of economic output" (OECD 2009). This statement, by focusing on the key role of biotechnologies, does not provide adequate space for the role of society and agriculture in the bioeconomy system (Hausknost et al 2017), which is defined as a technology-driven concept. Instead, BECOTEPS (BioEconomy Technology Platforms) defined bioeconomy as "… the sustainable production and conversion of biomass, for a range of food, health, fibre and industrial products and energy.…”
Section: Transition Dynamics In a Snm Approachmentioning
confidence: 99%
“…Moreover, the European Commission, in its official strategy -Innovating for Sustainable Growth: A Bioeconomy for Europe -stated that the bioeconomy "… encompasses the production of renewable biological resources and the conversion of these resources and waste streams into value added products, such as food, feed, bio-based products and bioenergy" (EU, 2012); here the definition focuses on value-added products. The two latter definitions emphasise a resource-driven concept based on the transition from a fossil-based to a bio-based economic system (Hausknost et al 2017).…”
Section: Transition Dynamics In a Snm Approachmentioning
confidence: 99%
See 1 more Smart Citation